2011
DOI: 10.1111/j.1753-4887.2011.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and body weight: a systematic review

Abstract: Based on the fact that energy content in 1 gram of alcohol is 29 kJ or 7.1 kcal, alcohol consumption can lead to weight gain. The present review was conducted to analyze the effects of alcohol consumption on body weight. A search of the Medline database for the period 1984 to March 2010 was conducted to identify cross-sectional, prospective cohort studies and intervention trials investigating the relationship between alcohol consumption and the risk of weight gain. Thirty-one publications were selected on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
234
4
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(256 citation statements)
references
References 55 publications
12
234
4
6
Order By: Relevance
“…Furthermore, it is known that individuals who are overweight and smoke increase the risk of developing some noncommunicable chronic diseases, among them cardiovascular diseases. (15) With respect to alcohol consumption, the study shows its association to excess weight, as it has also been shown by the systematic review by Sayon et al, (16) on this theme.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, it is known that individuals who are overweight and smoke increase the risk of developing some noncommunicable chronic diseases, among them cardiovascular diseases. (15) With respect to alcohol consumption, the study shows its association to excess weight, as it has also been shown by the systematic review by Sayon et al, (16) on this theme.…”
Section: Discussionsupporting
confidence: 50%
“…Evidence on the relationship of alcohol use and BMI is conflicting, with studies reporting no associations [64], positive associations [65] and negative associations [66]. However, a recent review by Traversy and Chaput (2015) [67] suggests that variations in this relationship may be a result of differences in the types of alcohol consumed, amount of alcohol per occasion, frequency of drinking and the differences in the alcohol metabolism between age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, some studies, in both men [49] and women [35,47], found no associations. Different patterns of consumption may be related to different outcomes [50].…”
Section: Could Alcohol Be a Risk Factor For Obesity?mentioning
confidence: 99%